Accommodating Students with Disabilities in Higher Education: Perception of Students with Disabilities Toward Faculty Willingness to Provide Academic Accommodation - Azzahrah, Anuar; Nor Mazlina, Ghazali; Edris, Aden (2017)
The needs for educational accommodations have become more salient since students with disabilities are often under presented in higher education setting in which have led these marginalized groups to unequal opportunities to participate in activities on campus thus, hindering their intellectual and psychological growth. The aim of the study was to identify the perception of students with disabilities toward faculty willingness to provide academic accommodation. A descriptive research design has been utilized in the study. 19 students with disabilities at Universiti Malaysia Sarawak (UNIMAS) were involved in the study. Based on the findings of the study, students have reported that the lecturers’ willingness to provide accommodation were moderate. Decreased motivation in learning, communication difficulties with the lecturers (faculty), and difficulty in accessing information and materials/sources related to academics were among the impacts of lack of academic accommodation on students with disabilities. Therefore, it is imperative for the faculty to identify the students’ academic accommodation needs because they would receive more information on how to improve their teaching and learning in the class especially when they deal with students with disabilities